Emerging Clinical Perspectives of Immunotherapy in Triple Negative Breast Cancer: A Comprehensive Review - Sparshita Dey; Sourav Maji; Soutrick Das; Souvik Kar; Sourish Dutta; Moumita Chowdhury (Journal of Clinical and Diagnostic Research)
A particularly aggressive and metastatic form of Breast Cancer (BC), known as triple-negative breast cancer (TNBC), is characterised by the absence of Hormone Receptors (HR). This subtype is associated with unfavourable outcomes and ineffective treatment options. Conventional treatments and surgical interventions often lead to therapy-induced resistance and suboptimal results. Nevertheless, the inherent immunogenicity of TNBC has paved the way for innovative immunotherapeutic approaches such as Immune Checkpoint Inhibitors (ICIs), cancer vaccines, and Chimeric Antigen Receptors T-cell (CAR-T) therapy. To critically assess the potential of immunotherapeutic strategies in overcoming the challenges associated with treating TNBC, this review includes exploring novel approaches in immunotherapy, identifying mechanisms of immune evasion, and evaluating the effectiveness of integrating biomarkers and multi-omics profiling to tailor therapies. A comprehensive review examined peer-reviewed literature from multiple databases, including Web of Science, Google Scholar, Scopus, and PubMed from 2002 to 2024. The review utilised key search phrases like “TNBC,” “ICIs,” “BC vaccines,” and “CAR-T therapy in BC.” Information on both approved and experimental treatments was obtained from https://clinicaltrials.gov/, https://www.fda.gov/, as well as from FDA and EMA reports. Study selection criteria were based on scientific quality, relevance, and citation impact. Out of 195 articles initially identified, 135 were ultimately included in the review. Recent research suggests that ICIs targeting programmed cell death protein (PD-1)/programmed cell death ligand (PD-L1) and cytotoxic T-lymphocyte associated protein 4 (CTLA-4) pathways enhance progression-free survival in certain TNBC patients, while CAR-T therapy and neoantigen vaccines boost antitumour immunity. Despite encouraging outcomes, obstacles such as tumour heterogeneity, unintended toxicity, and immune escape, largely influenced by an immunosuppressive Tumour Microenvironment (TME), continue to hinder therapeutic effectiveness. Improving TNBC treatment requires tackling immune evasion, enhancing biomarker-guided selection, and incorporating comprehensive multi-omics analysis. Resistance may be overcome through tailored immunotherapies, combined treatment approaches, and innovative drug delivery systems. This article explores ongoing clinical studies and upcoming trials focusing on ICIs, neoantigen-based vaccines, and CAR-T cell therapies, while also examining obstacles and tactics for boosting effectiveness.